Development of a hydraulic sub-model as part of a desktop environmental flow assessment method - Desai, Ahmed Yacoob (Rhodes University, Faculty of Science, Institute for Water Research, 2012)
Countries around the world have been developing ecological policies to protect their water resources and minimise the impacts of development on their river systems. The concept of 'minimum flows' was initially established as a solution but it did not provide sufficient protection as all elements of a flow regime were found to be important for the protection of the river ecosystem. "Environmental flows" were developed to determine these flow regimes to maintain a river in some defined ecological condition. Rapid, initial estimates of the quantity component of environmental flows may be determined using the Desktop Reserve Model in South Africa. However, the Desktop Reserve Model is dependent upon the characteristics of the reference natural hydrology used. The advancements in hydraulic and ecological relationships from the past decade have prompted the development of a Revised Desktop Reserve Model (RDRM) that would incorporate these relationships. The research in this thesis presents the development of the hydraulic sub-model for the RDRM. The hydraulic sub-model was designed to produce a realistic representation of the hydraulic conditions using hydraulic parameters/characteristics from readily available information for any part of South Africa. Hydraulic data from past EWR studies were used to estimate the hydraulic parameters. These estimated hydraulic parameters were used to develop hydraulic estimation relationships and these relationships were developed based on a combination of regression and rule-based procedures. The estimation relationships were incorporated into the hydraulic sub-model of the integrated RDRM and assessments of the hydraulic outputs and EWR results were undertaken to assess the 'applicability' of the hydraulic sub-model. The hydraulic sub-model was assessed to be at a stage where it can satisfactorily be incorporated in the RDRM and that it is adequately robust in many situations. Recommendations for future work include the refinement of estimation of the channel forming discharge or the use of spatial imagery to check the maximum channel width estimation. It is also proposed that a future version of the hydraulic sub-model could include flow regime change impacts on channel geomorphology and sedimentology so that flow management scenarios can be more effectively assessed.
Keywords: Hydrologic models -- Research -- South Africa; Hydraulic engineering -- South Africa; Rivers -- South Africa